Eco-friendly methods for extraction and modification of cellulose: an overview - Magalhães, Solange (2023)
Cellulose is the most abundant renewable polymer on Earth and can be obtained from several different sources, such as trees, grass, or biomass residues. However, one of the issues is that not all the fractionation processes are eco-friendly and are essentially based on cooking the lignocellulose feedstock in a harsh chemical mixture, such as NaOH + Na2S, and water, to break loose fibers. In the last few years, new sustainable fractionation processes have been developed that enable the obtaining of cellulose fibers in a more eco-friendly way. As a raw material, cellulose’s use is widely known and established in many areas. Additionally, its products/derivatives are recognized to have a far better environmental impact than fossil-based materials. Examples are textiles and packaging, where forest-based fibers may contribute to renewable and biodegradable substitutes for common synthetic materials and plastics. In this review, some of the main structural characteristics and properties of cellulose, recent green extraction methods/strategies, chemical modification, and applications of cellulose derivatives are discussed.